Economic effects of COVID-19 on private sector entrepreneurs, Huánuco, 2020 - Vargas-Tarazona, Beatriz E. (2021)
Objective. To analyze the impact of COVID-19 on the entrepreneurs of MYPES, clients of the accounting firm C-PROVICSA, Huanuco, 2020. Methods. Methods. The study had a quantitative approach, applied type, non-experimental design and the study method was descriptive. The population consisted of 115 entrepreneurs of MYPES that received advice from the accounting firm C-PROVICSA in the period 2020 in the province of Huánuco. Was formed by 104 entrepreneurs of the MYPES. A survey prepared by the researchers was used and validated by expert judgement. To determine the degree of reliability of the model Cronbach alpha procedure was applied, which resulted in 0.635. In this sense, to describe the behavior of the variable "economic effects of COVID-19 in Huanhua companies", the instrument used was a questionnaire, which had 18 items that were answered with the purpose of treating the three dimensions of the study variable: spread of the disease, suspension of activities, and social distancing. Results. The results obtained showed that the economic effects caused by the COVID-19 sanitary emergency had a negative impact on the business development of the clients of the C-PROVICSA accounting firm. Conclusions. There is a considerable impact on the economic income and a low demand for its products in the current context.